2014
DOI: 10.1136/jclinpath-2013-202092
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and molecular characterisation of the sessile serrated adenoma in a subset of the Chinese population

Abstract: The prevalence of SSAs in a subset of the Chinese population is much lower than that in the Western population. BRAF((V600E)) mutation is not a frequent event in right colon serrated polyps in a subset of the Chinese population. APC mutation is possibly the main cause for the Wnt signalling activation in right colon serrated polyps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…The prevalence of SSA/P in our population was 1.4%, and this result was consistent with previous studies. 26,27 The present study included asymptomatic subjects who received screening colonoscopy as part of a general health checkup not specific for CRC screening, therefore minimizing the possibility of bias. Moreover, positivity rates of 10.4%, 6.2%, and 5.0% at cutoffs of 10, 15, and 20 mg/g, respectively, are within the range of FIT positivity reported by several FIT-based screening programs or trials in the general population, 3,18,28 which again supports our cohort as representative of the general population.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of SSA/P in our population was 1.4%, and this result was consistent with previous studies. 26,27 The present study included asymptomatic subjects who received screening colonoscopy as part of a general health checkup not specific for CRC screening, therefore minimizing the possibility of bias. Moreover, positivity rates of 10.4%, 6.2%, and 5.0% at cutoffs of 10, 15, and 20 mg/g, respectively, are within the range of FIT positivity reported by several FIT-based screening programs or trials in the general population, 3,18,28 which again supports our cohort as representative of the general population.…”
Section: Discussionmentioning
confidence: 99%
“…[ 40 41 ] Some studies in Chinese population also suggested the similar low prevalence of SSA/Ps. [ 42 43 ] Various factors including the patients’ population, colonoscopy quality, pathologic validation, variation between centers, and ethnicity might cause these differences. [ 10 21 ] In addition, inadequate communication between pathologists and endoscopists, ignorance of inconspicuous rectal polyps, and lack of validated classification criterion may also contribute to the missing rate in Chinese patients.…”
Section: Discussionmentioning
confidence: 99%
“…[2225] One Chinese study reported a 14.3% BRAF V600E mutation rate in SSA, which is a lower rate than in the Western population. [26] One Korean study reported that BRAF V600E mutations are found in 43.5% to 58.3% of TSAs. [27] In our study, the rates of BRAF V600E mutation were 47.2% in TSA and 41.2% in SSA, consistent with other studies.…”
Section: Discussionmentioning
confidence: 99%